Carbon-carbon loaded WC / Bi2MoO6 composite photoelectrocatalysis photocathode and preparation method thereof

By layering the growth of Bi2MoO6 and WC on carbon-carbon composite materials, forming WC/Bi2MoO6/C-C composite photocatalytic photocathode, the serious photogenerated electron-hole recombination in the existing photoelectrocatalytic water decomposition technology is solved, and efficient solar-to-hydrogen energy conversion is achieved.

CN119843319APending Publication Date: 2025-04-18SHAANXI UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510118535.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing photoelectrocatalytic water decomposition technology has problems such as severe photogenerated electron-hole recombination, low carrier mobility, and slow water oxidation kinetics, resulting in low solar-hydrogen conversion efficiency, limiting the large-scale application of the technology.

Method used

By layering the growth of Bi2MoO6 and WC on a carbon-carbon composite material (C-C), forming a WC/Bi2MoO6/C-C composite photoelectrocatalytic photocathode, the material was prepared by a two-step method of hydrothermal deposition and electrophoretic deposition to form a heterostructure to improve conductivity and reaction kinetics.

Benefits of technology

It achieves high conductivity, good reaction kinetics, high stability and excellent hydrogen evolution performance, and improves the efficiency of photoelectrocatalytic water decomposition.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843319A_ABST
    Figure CN119843319A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon-carbon-loaded WC / Bi2MoO6 composite photoelectrocatalysis photocathode and a preparation method thereof, and belongs to the field of composite photoelectrocatalysis photocathode preparation, and the method comprises the following steps: sequentially oxidizing and etching the surface of a carbon-carbon composite material, immersing the carbon-carbon composite material in a mixed solution of bismuth trichloride and sodium molybdate for hydrothermal reaction, and then washing and drying to obtain the carbon-carbon-loaded WC / Bi2MoO6 composite photoelectrocatalysis photocathode. The Bi2MoO6 composite material loaded with carbon and carbon is obtained; the preparation method comprises the following steps: uniformly dispersing WC powder and polyacrylamide in isopropanol, then adding elemental iodine, uniformly dispersing to obtain a WC precursor solution, depositing WC on the surface of Bi2MoO6 by using the WC precursor solution in an electrophoretic deposition manner, and keeping the temperature of the obtained compound at 300-500 DEG C for 1-4 hours in an inert atmosphere to obtain the carbon-carbon loaded WC / Bi2MoO6 composite photoelectrocatalysis photocathode. The material shows good photoelectrocatalytic hydrogen evolution performance in an alkaline solution, and is an efficient PEC catalytic material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of composite photoelectrocatalytic photocathode preparation, and relates to a carbon-carbon loaded WC / Bi2MoO6 composite photoelectrocatalytic photocathode and a preparation method thereof. Background Art

[0002] With the increasing consumption of traditional fossil energy, energy crisis and environmental pollution are becoming increasingly serious. In this context, the conversion and utilization of solar energy as a clean and renewable energy is particularly important and is closely linked to environmental protection and water purification. Further development of low-carbon, environmentally friendly green energy, as well as corresponding energy storage and conversion technologies, is essential for sustainable energy utilization. Compared with other green energy sources (such as solar energy, wind energy, hydropower and tidal energy), hydrogen energy is considered to be a more efficient and cost-effective energy source that is expected to meet the growing energy demand. PEC cells can convert solar energy into chemical energy cleanly and sustainably. At present, photoelectrocatalytic water splitting technology generally has problems such as severe photogenerated electron-hole recombination, low carrier mobility, and slow water oxidation kinetics, resulting in low solar-to-hydrogen energy conversion efficiency (STH), which greatly limits the large-scale application of photoelectrocatalytic water splitting technology. Therefore, technicians have explored and prepared different photoanode materials.

[0003] Among the many photoanodes, bismuth molybdate has attracted widespread attention due to its high theoretical photocurrent density, stable chemical properties, and small band gap. Bismuth molybdate has three different crystal forms with different band gap values, absorption coefficients, and charge transfer properties. The photoelectrocatalytic properties of the three also show great differences. Among them, the γ phase (Bi2MoO6) exhibits excellent photoelectrocatalytic properties due to its unique Aurivillius layered compound structure, orthorhombic crystal form, good thermal stability, and low color permeability. However, the rapid recombination of its photogenerated carriers and the slow surface oxidation kinetics severely inhibit the water oxidation of the bismuth molybdate (γ-Bi2MoO6) photoanode photoelectrochemical (PEC).

[0004] There are many ways to improve the catalytic performance of Bi2MoO6 photoanodes, such as morphology control, ion doping, heterostructure construction and co-catalyst loading. Transition metal carbides (TMCs) are widely used in chemical engineering, electronic devices and other fields due to their advantages such as high conductivity, high hardness, acid and alkali resistance and good thermal stability. Transition metal carbides (TMCs) usually have high hardness, clear crystal structure, high thermal stability, good chemical corrosion resistance and excellent conductivity, which makes them ideal support materials. WC-based materials are considered to be a promising Pt-alternative electrocatalyst because of their similar electronic structure to Pt at the Fermi level, low cost and good corrosion resistance. Carbon-carbon substrates (CCs) have high specific surface area, high electronic conductivity and 3D open pore structure, which further improves the exposure of product active sites and is conducive to the improvement of photoelectrocatalytic performance.

[0005] Therefore, if Bi2MoO6 and WC are grown in layers on CC, it is possible to generate a WC / Bi2MoO6 / CC composite photoelectrocatalytic photocathode from a theoretical perspective, in which the heterostructure formed by Bi2MoO6 and WC can enhance the electronic interaction at the two-phase heterogeneous interface and improve the overall conductivity. The prepared WC / Bi2MoO6 / CC composite photoelectrocatalytic photocathode has high conductivity, good reaction kinetics, high stability and high hydrogen evolution efficiency, but no related reports have been seen so far. Summary of the invention

[0006] In view of the problems existing in the prior art, the present invention provides a carbon-carbon loaded WC / Bi2MoO6 composite photoelectrocatalytic photocathode and a preparation method thereof. Bi2MoO6 and WC are layered and grown on a carbon-carbon composite material (CC) by a two-step method mainly using hydrothermal deposition and electrophoretic deposition. The prepared WC / Bi2MoO6 / CC photoelectrocatalytic material has a controllable structure and exhibits good photoelectrocatalytic hydrogen evolution performance in alkaline solution, and is a highly efficient PEC catalytic material.

[0007] The present invention is achieved through the following technical solutions: A method for preparing a carbon-carbon loaded WC / Bi2MoO6 composite photoelectrocatalytic photocathode comprises the following steps: Step 1, oxidizing and etching the surface of the carbon-carbon composite material in sequence, and then immersing it in a mixed solution of bismuth trichloride and sodium molybdate, wherein the molar ratio of bismuth trichloride to sodium molybdate is 2:(1-5), and performing a hydrothermal reaction at 100-200 °C, followed by washing and drying to obtain a carbon-carbon supported Bi2MoO6 composite material; Step 2, uniformly dispersing WC powder and polyacrylamide in isopropanol, then adding iodine and uniformly dispersing them to obtain a WC precursor solution, and then using the WC precursor solution to deposit WC on the Bi2MoO6 surface of the carbon-carbon-loaded Bi2MoO6 composite material by electrophoretic deposition to obtain a composite; Step 3, the composite is kept at 300-500 °C for 1-4 h under the protection of an inert atmosphere to obtain a carbon-carbon loaded WC / Bi2MoO6 composite photoelectrocatalytic photocathode.

[0008] Preferably, the mixed solution of bismuth trichloride and sodium molybdate in step 1 is obtained by the following process: Sodium molybdate and bismuth trichloride are sequentially added to deionized water, and then ethylene glycol is added, the volume ratio of ethylene glycol to deionized water is (5-20): (20-80), and finally stirred for 20-60 minutes to obtain a mixed solution of bismuth trichloride and sodium molybdate.

[0009] Preferably, in step 1, the surface of the carbon-carbon composite material is oxidized according to the following process: The carbon-carbon composite material is heated to 300-700 °C and then kept warm for 1-30 min to obtain a carbon-carbon composite material after pre-oxidation treatment, thereby completing the oxidation of the surface of the carbon-carbon composite material.

[0010] Furthermore, in step 1, the pre-oxidized carbon-carbon composite material is immersed in acetone for 12 to 48 hours, then immersed in hydrogen peroxide for 2 to 12 hours, then ultrasonically treated with deionized water and anhydrous ethanol for 15 to 30 minutes respectively, and finally immersed in a mixed solution of bismuth trichloride and sodium molybdate.

[0011] Furthermore, in step 1, the surface of the carbon-carbon composite material is oxidized and etched in sequence, and then immersed in a mixed solution of bismuth trichloride and sodium molybdate, hydrothermally reacted at 100-200° C. for 6-36 hours, and then washed and dried.

[0012] Further, the WC powder described in step 2 is obtained according to the following steps: Ammonium tungstate and dicyandiamide are mixed uniformly in a mass ratio of (0.1~1): (1~5), and under the protection of an inert atmosphere, the temperature is raised from room temperature to 800~1300 °C at a heating rate of 5~20 °C / min, and then kept warm for 2~4 h. After cooling, the mixture is ground to obtain WC powder.

[0013] Further, the WC precursor solution described in step 2 is obtained according to the following steps: 20 mL~60 mL of isopropanol and 0.001~0.03 g of polyacrylamide are added to every 0.2~0.8 g of WC powder, and the mixture is stirred until uniformly dispersed. Then, 0.2~0.8 g of iodine is added and the mixture is stirred until uniformly dispersed to obtain a WC precursor solution.

[0014] Further, in step 2, the carbon-carbon loaded Bi2MoO6 composite material is placed at the negative electrode of an electrophoretic deposition apparatus, and a WC precursor solution is used for deposition at a voltage of 1 to 30 V and a current of 0.1 to 2 A for 30 s to 1 h to obtain a composite.

[0015] Furthermore, in step 3, the temperature of the composite is raised from room temperature to 300-500 °C at a heating rate of 5-20 °C / min, and then kept warm for 1-4 h to obtain a carbon-carbon loaded WC / Bi2MoO6 composite photoelectrocatalytic photocathode.

[0016] A carbon-carbon loaded WC / Bi2MoO6 composite photoelectrocatalytic photocathode is obtained based on the preparation method of a carbon-carbon loaded WC / Bi2MoO6 composite photoelectrocatalytic photocathode described in any one of the above items.

[0017] Compared with the prior art, the present invention has the following beneficial technical effects: The present invention discloses a method for preparing a carbon-carbon loaded WC / Bi2MoO6 composite photoelectrocatalytic photocathode, wherein the surface of the carbon-carbon composite material is oxidized and etched in sequence, wherein oxidation can improve the interface characteristics between the substrate and the subsequently grown or deposited WC / Bi2MoO6, reduce interface defects and stress, and improve the quality and performance of the heterogeneous structure, and oxidation can slightly etch the surface of the carbon-carbon substrate so that the surface roughness is adjusted. Appropriate roughness is conducive to increasing the mechanical engagement with WC / Bi2MoO6 and improving the overall performance of the composite material, and then the Bi2MoO6 / CC catalyst is prepared by deposition on a CC substrate in a hydrothermal manner, and the reaction conditions are mild and easy to implement. By introducing polyacrylamide and iodine element into WC powder, a WC precursor solution is obtained that is conducive to subsequent electrophoretic deposition, and then by means of electrophoretic deposition, WC is grown on Bi2MoO6 / CC using the WC precursor solution, so that the CC substrate can be well layered and coated. The present invention uses CC material as a carrier. Since the CC substrate is acid-resistant and alkali-resistant, the structure of the self-supporting carbon-carbon loaded WC / Bi2MoO6 composite photoelectrocatalytic photocathode can be controlled (the hydrothermal method loads bismuth molybdate on carbon-carbon, and the thickness of Bi2MoO6 can be changed by changing the hydrothermal time, and the charge of particles in the WC precursor solution can be changed. The more charged, the faster the particles move. Then, the deposition voltage and current are changed by electrophoretic deposition technology, which can better load on the substrate, and the deposition time further changes the thickness of Bi2MoO6 / CC), and has good stability under alkaline conditions. The CC substrate has a large specific surface area, which can effectively increase the number of active sites of the composite photoelectrocatalyst. At the same time, the composite of Bi2MoO6 and WC on the CC substrate can form a heterogeneous structure, which can enhance the electronic interaction of the two-phase heterogeneous interface, improve the overall conductivity, and effectively enhance the transmission of electrons, so that the WC / Bi2MoO6 / CC composite photoelectrocatalytic photocathode exhibits high conductivity, good reaction kinetics, high stability and excellent hydrogen evolution performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is the XRD spectrum of Bi2MoO6 powder in the Bi2MoO6 / CC catalyst prepared under the conditions of Example 2 of the present invention.

[0019] Figure 2 This is the XRD pattern of WC prepared under the conditions of Example 2 of the present invention.

[0020] Figure 3 This is a SEM photograph of WC / Bi2MoO6 / CC prepared under the conditions of Example 2 of the present invention.

[0021] Figure 4This is the LSV performance diagram of hydrogen evolution under alkaline conditions of WC / Bi2MoO6 / CC prepared under the conditions of Example 2 of the present invention.

[0022] Figure 5 This is the IT performance diagram of WC / Bi2MoO6 / CC prepared under the conditions of Example 2 of the present invention. DETAILED DESCRIPTION

[0023] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.

[0024] The present invention provides a method for preparing a carbon-carbon loaded WC / Bi2MoO6 composite photoelectrocatalytic photocathode, comprising the following steps: Step 1, weigh analytically pure bismuth trichloride and sodium molybdate, wherein the molar ratio of bismuth trichloride to sodium molybdate is 2:(1-5), add sodium molybdate and bismuth trichloride to 20-80 mL of deionized water in sequence, and then add 5-20 mL of ethylene glycol, which has good solubility and can promote the dispersion and dissolution of sodium molybdate and bismuth trichloride, improve the stability and uniformity of the solution, and stir for 20-60 min to form a uniformly mixed solution A; Step 2: Take the density as 1.1-1.3g / cm 3 The low-density CC substrate is a reinforcement made of woven carbon fibers. The carbon-carbon composite material is formed by solidifying and carbonizing the carbon fiber fabric through a liquid phase impregnation-carbonization process. The substrate is cut into a length of 2-7 cm and a width of 1-3 cm, placed in a magnetic boat, and placed in a muffle furnace. The temperature is raised to 300-700 °C and kept warm for 1-30 min. The surface of the CC substrate is pre-oxidized to improve the interface characteristics between the substrate and the subsequently grown or deposited WC / Bi2MoO6, reduce interface defects and stress, and improve the quality and performance of the heterogeneous structure. Step 3, take another 50 mL beaker, immerse the pretreated CC substrate completely in acetone for 12-48 h, and then immerse it in hydrogen peroxide for 2-12 h. The oxidation of hydrogen peroxide can slightly etch the surface of the carbon-carbon substrate to adjust the surface roughness. Appropriate roughness is conducive to increasing the mechanical bite with WC / Bi2MoO6 and improving the overall performance of the composite material. Then, ultrasonic treatment with deionized water and anhydrous ethanol for 15-30 min respectively; Step 4, put solution A into the polytetrafluoroethylene liner, put the treated CC substrate into the liner, put the sealed high-pressure reactor into the homogeneous hydrothermal reactor, set the temperature parameter to 100-200 °C, and the reaction time to 6-36 h; Step 5, after the reaction is completed, cool to room temperature, take out the substrate with tweezers, wash it with anhydrous ethanol and deionized water for 3-5 times respectively, and dry it in a 40-100 ℃ oven for 2-6 h to obtain CC-loaded Bi2MoO6 catalyst, denoted as B, which is Bi2MoO6 / CC catalyst; Step 6, weigh ammonium tungstate and dicyandiamide, mix them in a mass ratio of (0.1-1): (1-5), mix them evenly, place them in a white magnetic boat, put them in a tube furnace, and under the protection of an inert atmosphere of Ar, heat them from room temperature to 800-1300 °C at a heating rate of 5-20 °C / min, keep them warm for 2-4 h, and after the product is cooled with the furnace, take it out and grind it to obtain powder C, i.e. WC powder; The WC material is prepared by a one-step calcination method, and the WC material with good crystallinity is prepared by controlling the reaction temperature and time. Step 7, weigh 0.2-0.8 g of powder C and place it in a beaker, then add 20 mL-60 mL of isopropanol and 0.001-0.03 g of PAM (polyacrylamide) in sequence, stir until uniformly dispersed, then add 0.2-0.8 g of iodine and continue stirring until uniformly dispersed, to obtain a WC precursor solution; Step 8, place the CC substrate loaded with Bi2MoO6 on the negative electrode of the electrophoretic deposition instrument, use a 20*10*3 mm graphite substrate as the positive electrode, set the voltage to 1~30 V and the current to 0.1~2 A, then turn on the equipment, deposit the WC precursor solution for 30 s~1 h, then turn off the equipment and take out the precursor D; The thickness of the product can be well controlled by controlling the deposition time.

[0025] Step 9, place the precursor D in a white magnetic boat, put it into a tubular furnace, and under the protection of an inert atmosphere of Ar, heat the temperature from room temperature to 300-500 °C at a rate of 5-20 °C / min, and keep it warm for 1-4 h. The high temperature during the calcination process can promote the interfacial reaction between different phases in the composite material, form chemical bonds or other strong interactions at the interface, thereby enhancing the bonding force between the phases and improving the overall performance and stability of the composite material, so as to obtain the desired carbon-carbon loaded WC / Bi2MoO6 composite photoelectrocatalytic photocathode. Example 1 Step 1, weigh analytically pure bismuth trichloride and sodium molybdate, wherein the molar ratio of bismuth trichloride to sodium molybdate is 2:1, add sodium molybdate and bismuth trichloride to 20 mL of deionized water in sequence, then add 5 mL of ethylene glycol solution, and stir for 20 minutes to form a uniformly mixed solution A; Step 2: Take the density as 1.1 g / cm 3The low-density CC substrate was cut into 2 cm in length and 1 cm in width, placed in a magnetic boat, put into a muffle furnace, heated to 300 °C, and kept warm for 1 min to pre-oxidize the CC substrate; Step 3, take another 50 mL beaker, immerse the pretreated CC substrate completely in acetone for 12 h, then in hydrogen peroxide for 2 h, and then ultrasonically treat with deionized water and anhydrous ethanol for 15 min respectively; Step 4, put solution A into the polytetrafluoroethylene liner, put the treated CC substrate into the liner, put the sealed high-pressure reactor into the homogeneous hydrothermal reactor, set the temperature parameter to 100 °C, and the reaction time to 6 h; Step 5, after the reaction is completed, the substrate is cooled to room temperature, and the substrate is taken out with tweezers, and then washed with anhydrous ethanol and deionized water for 3 times, respectively, and dried in a 40 °C oven for 2 h to obtain a CC-loaded Bi2MoO6 catalyst, denoted as B, which is a Bi2MoO6 / CC catalyst; Step 6, weigh ammonium tungstate and dicyandiamide, mix them in a mass ratio of 0.1: 1, put them in a white magnetic boat, put them in a tube furnace, and under the protection of an inert atmosphere of Ar, heat them from room temperature to 800 ° C at a rate of 5 ° C / min, keep them warm for 2 h, and after the product is cooled with the furnace, take it out and grind it to obtain powder C, that is, WC powder; Step 7, weigh 0.2 g of powder C and place them in a beaker, then add 20 mL of isopropanol and 0.001 g of PAM (polyacrylamide) in sequence, stir until uniformly dispersed, then add 0.2 g of iodine and continue stirring until uniformly dispersed, to obtain a WC precursor solution; Step 8, place the CC substrate loaded with Bi2MoO6 on the negative electrode of the electrophoretic deposition instrument, use a 20*10*3 mm graphite substrate on the positive electrode, set the voltage to 1 V and the current to 0.1 A, then turn on the equipment, deposit the WC precursor solution for 30 s, then turn off the equipment and take out the precursor D; Step 9, place the precursor D in a white magnetic boat, put it into a tubular furnace, and under the protection of an inert atmosphere of Ar, heat the temperature from room temperature to 300 °C at a rate of 5 °C / min, and keep it warm for 1 h to obtain the desired carbon-carbon loaded WC / Bi2MoO6 composite photoelectrocatalytic photocathode. Example 2 Step 1, weigh analytically pure bismuth trichloride and sodium molybdate, wherein the molar ratio of bismuth trichloride to sodium molybdate is 2:3, add sodium molybdate and bismuth trichloride to 40 mL of deionized water in sequence, then add 10 mL of ethylene glycol solution, and stir for 40 minutes to form a uniformly mixed solution A; Step 2: Take the density as 1.2 g / cm3 The low-density CC substrate was cut into 5 cm in length and 2 cm in width, placed in a magnetic boat, put into a muffle furnace, heated to 500 °C, and kept warm for 10 min to pre-oxidize the CC substrate; Step 3, take another 50 mL beaker, immerse the pretreated CC substrate completely in acetone for 24 h, then in hydrogen peroxide for 6 h, and then ultrasonically treat with deionized water and anhydrous ethanol for 20 min respectively; Step 4, put solution A into the polytetrafluoroethylene liner, put the treated CC substrate into the liner, put the sealed high-pressure reactor into the homogeneous hydrothermal reactor, set the temperature parameter to 150 ° C, and the reaction time to 24 h; Step 5, after the reaction is completed, the substrate is cooled to room temperature, and the substrate is taken out with tweezers, and then washed with anhydrous ethanol and deionized water for 4 times, respectively, and dried in a 60 ° C oven for 4 h to obtain a CC-loaded Bi2MoO6 catalyst, denoted as B, which is a Bi2MoO6 / CC catalyst; Step 6, weigh ammonium tungstate and dicyandiamide, mix them in a mass ratio of 0.5: 2, put them in a white magnetic boat, put them in a tube furnace, and under the protection of an inert atmosphere of Ar, heat them from room temperature to 1000°C at a rate of 10°C / min, keep them warm for 3 h, and after the product is cooled with the furnace, take it out and grind it to obtain powder C, i.e. WC powder; Step 7, weigh 0.6 g of powder C and place them in a beaker, then add 40 mL of isopropanol and 0.02 g of PAM (polyacrylamide) in sequence, stir until uniformly dispersed, then add 0.6 g of iodine and continue stirring until uniformly dispersed, to obtain a WC precursor solution; Step 8, place the CC substrate loaded with Bi2MoO6 at the negative electrode of the electrophoretic deposition instrument, use a 20*10*3 mm graphite substrate as the positive electrode, set the voltage to 20 V and the current to 1 A, then turn on the equipment, deposit the WC precursor solution for 0.5 h, then turn off the equipment and take out the precursor D; Step 9, place the precursor D in a white magnetic boat, put it into a tubular furnace, and under the protection of an inert atmosphere of Ar, heat the temperature from room temperature to 400 °C at a rate of 10 °C / min, and keep it warm for 2 h to obtain the desired carbon-carbon loaded WC / Bi2MoO6 composite photoelectrocatalytic photocathode (for convenience, denoted as WC / Bi2MoO6 / CC).

[0026] The hydrothermal carbon matrix was placed in ethanol and ultrasonically dried to obtain a powder, which was then subjected to XRD testing. Figure 1 ,Depend on Figure 1It can be seen that the ultrasonically captured powder corresponds well to the Bi2MoO6PDF#21-0102 card, indicating that the Bi2MoO6 powder is successfully loaded on the carbon substrate.

[0027] from Figure 2 It can be seen that the calcined powder can correspond well to the WCPDF#99-000-3892 card, indicating that the WC powder was successfully prepared.

[0028] from Figure 3 It can be seen that there are obvious flaky and blocky powders on the carbon substrate, while the microstructure of Bi2MoO6 is flaky and the microstructure of WC powder is blocky, indicating that Bi2MoO6 powder and WC powder are successfully loaded on the carbon substrate.

[0029] In an alkaline solution of 1M KOH pH=14, the working electrode, i.e. the prepared WC / Bi2MoO6 / CC electrode, the reference electrode, saturated calomel, and the counter electrode, a carbon rod, were placed in an electrolytic cell. The working electrode was illuminated by a light source, and a bias voltage was applied through an electrochemical workstation to obtain Figure 4 The photocurrent response curve of hydrogen evolution in the graph shows that at 100 mA / cm 2 At this current density, the overpotential of the electrode is 283 mV.

[0030] The IT curve (current density-time curve) in the hydrogen evolution test is an important tool for analyzing the hydrogen evolution performance. Under the same conditions as above, at a set constant potential, the electrochemical workstation is used to record the change of current density over time to obtain Figure 5 The it curve. Figure 5 It can be seen that the electrode is -0.04mA / cm 2 At the current density, it can run stably for at least 4 h.

[0031] Example 3 Step 1, weigh analytically pure bismuth trichloride and sodium molybdate, wherein the molar ratio of bismuth trichloride to sodium molybdate is 2:5, add sodium molybdate and bismuth trichloride to 80 mL of deionized water in sequence, then add 20 mL of ethylene glycol solution, and stir for 60 minutes to form a uniformly mixed solution A; Step 2: Take the density as 1.3 g / cm 3 The low-density CC substrate was cut into 7 cm in length and 3 cm in width, placed in a magnetic boat, put into a muffle furnace, heated to 700 °C, and kept warm for 30 min to pre-oxidize the CC substrate; Step 3, take another 50 mL beaker, immerse the pretreated CC substrate completely in acetone for 48 h, then immerse it in hydrogen peroxide for 12 h, and then ultrasonically treat it with deionized water and anhydrous ethanol for 30 min respectively; Step 4, solution A is placed in a polytetrafluoroethylene liner, and the treated CC substrate is placed in the liner, and the sealed high-pressure reactor is placed in a homogeneous hydrothermal reactor, and the temperature parameters are set to 200 °C and the reaction time is 36 h; Step 5, after the reaction is completed, cool to room temperature, take out the substrate with tweezers, wash it with anhydrous ethanol and deionized water for 5 times, and dry it in an oven at 100 °C for 6 h to obtain a CC-supported Bi2MoO6 catalyst, denoted as B, which is a Bi2MoO6 / CC catalyst; Step 6, weigh ammonium tungstate and dicyandiamide, mix them in a mass ratio of 1: 5, put them in a white magnetic boat, put them in a tube furnace, and under the protection of an inert atmosphere of Ar, heat them from room temperature to 1300 ° C at a rate of 20 ° C / min, keep them warm for 4 h, and after the product is cooled with the furnace, take it out and grind it to obtain powder C, that is, WC powder; Step 7, weigh 0.8 g of powder C and place them in a beaker, then add 60 mL of isopropanol and 0.03 g of PAM (polyacrylamide) in sequence, stir until uniformly dispersed, then add 0.8 g of iodine and continue stirring until uniformly dispersed, to obtain a WC precursor solution; Step 8, place the CC substrate loaded with Bi2MoO6 on the negative electrode of the electrophoretic deposition instrument, use a 20*10*3 mm graphite substrate on the positive electrode, set the voltage to 30 V and the current to 2 A, then turn on the equipment, deposit the WC precursor solution for 1 h, then turn off the equipment and take out the precursor D; Step 9, place the precursor D in a white magnetic boat, put it into a tubular furnace, and under the protection of an inert atmosphere of Ar, raise the temperature from room temperature to 500 °C at a rate of 20 °C / min, and keep it warm for 4 h to obtain the desired carbon-carbon loaded WC / Bi2MoO6 composite photoelectrocatalytic photocathode.

Claims

1. A method for preparing a carbon-carbon loaded WC / Bi2MoO6 composite photoelectrocatalytic photocathode, characterized in that: The following steps are involved: Step 1, oxidizing and etching the surface of the carbon-carbon composite material in sequence, and then immersing it in a mixed solution of bismuth trichloride and sodium molybdate, wherein the molar ratio of bismuth trichloride to sodium molybdate is 2:(1-5), and performing a hydrothermal reaction at 100-200 °C, followed by washing and drying to obtain a carbon-carbon supported Bi2MoO6 composite material; Step 2, uniformly dispersing WC powder and polyacrylamide in isopropanol, then adding iodine and uniformly dispersing them to obtain a WC precursor solution, and then using the WC precursor solution to deposit WC on the Bi2MoO6 surface of the carbon-carbon-loaded Bi2MoO6 composite material by electrophoretic deposition to obtain a composite; Step 3, the composite is kept at 300-500 °C for 1-4 h under the protection of an inert atmosphere to obtain a carbon-carbon loaded WC / Bi2MoO6 composite photoelectrocatalytic photocathode.

2. The method for preparing a carbon-carbon loaded WC / Bi2MoO6 composite photoelectrocatalytic photocathode according to claim 1, characterized in that: The mixed solution of bismuth trichloride and sodium molybdate described in step 1 is obtained by the following process: Sodium molybdate and bismuth trichloride are sequentially added to deionized water, and then ethylene glycol is added, the volume ratio of ethylene glycol to deionized water is (5-20): (20-80), and finally stirred for 20-60 minutes to obtain a mixed solution of bismuth trichloride and sodium molybdate.

3. The method for preparing a carbon-carbon loaded WC / Bi2MoO6 composite photoelectrocatalytic photocathode according to claim 1, characterized in that: Step 1: Oxidize the surface of the carbon-carbon composite material according to the following process: The carbon-carbon composite material is heated to 300-700 °C and then kept warm for 1-30 min to obtain a carbon-carbon composite material after pre-oxidation treatment, thereby completing the oxidation of the surface of the carbon-carbon composite material.

4. The method for preparing a carbon-carbon loaded WC / Bi2MoO6 composite photoelectrocatalytic photocathode according to claim 3, characterized in that: Step 1: Immerse the pre-oxidized carbon-carbon composite material in acetone for 12 to 48 hours, then immerse it in hydrogen peroxide for 2 to 12 hours, then ultrasonically treat it with deionized water and anhydrous ethanol for 15 to 30 minutes respectively, and finally immerse it in a mixed solution of bismuth trichloride and sodium molybdate.

5. The method for preparing a carbon-carbon loaded WC / Bi2MoO6 composite photoelectrocatalytic photocathode according to claim 1, characterized in that: Step 1: The surface of the carbon-carbon composite material is oxidized and etched in sequence, then immersed in a mixed solution of bismuth trichloride and sodium molybdate, hydrothermally reacted at 100-200° C. for 6-36 hours, and then washed and dried.

6. The method for preparing a carbon-carbon loaded WC / Bi2MoO6 composite photoelectrocatalytic photocathode according to claim 1, characterized in that: The WC powder described in step 2 is obtained by the following steps: Ammonium tungstate and dicyandiamide are mixed uniformly in a mass ratio of (0.1~1): (1~5), and under the protection of an inert atmosphere, the temperature is raised from room temperature to 800~1300 °C at a heating rate of 5~20 °C / min, and then kept warm for 2~4 h. After cooling, the mixture is ground to obtain WC powder.

7. The method for preparing a carbon-carbon loaded WC / Bi2MoO6 composite photoelectrocatalytic photocathode according to claim 6, characterized in that: The WC precursor solution described in step 2 is obtained by the following steps: 20 mL~60 mL of isopropanol and 0.001~0.03 g of polyacrylamide are added to every 0.2~0.8 g of WC powder, and the mixture is stirred until uniformly dispersed. Then, 0.2~0.8 g of iodine is added and the mixture is stirred until uniformly dispersed to obtain a WC precursor solution.

8. The method for preparing a carbon-carbon loaded WC / Bi2MoO6 composite photoelectrocatalytic photocathode according to claim 1, characterized in that: Step 2: Place the carbon-carbon loaded Bi2MoO6 composite material at the negative electrode of an electrophoretic deposition apparatus, and use a WC precursor solution to deposit for 30 s to 1 h at a voltage of 1 to 30 V and a current of 0.1 to 2 A to obtain a composite.

9. The method for preparing a carbon-carbon loaded WC / Bi2MoO6 composite photoelectrocatalytic photocathode according to claim 1, characterized in that: Step 3: The temperature of the composite is raised from room temperature to 300-500 °C at a heating rate of 5-20 °C / min, and then kept warm for 1-4 h to obtain a carbon-carbon loaded WC / Bi2MoO6 composite photoelectrocatalytic photocathode.

10. A carbon-carbon loaded WC / Bi2MoO6 composite photoelectrocatalytic photocathode, obtained based on the preparation method of a carbon-carbon loaded WC / Bi2MoO6 composite photoelectrocatalytic photocathode according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Bi2MoO6 / CuO photoelectrode film, preparation method thereof and application of Bi2MoO6 / CuO photoelectrode film in photoelectrochemical water decomposition

    CN114737217A

  • Method for preparing WC / C electrode material by utilizing hydrothermal electrophoretic deposition

    CN117418263A

  • Bi2MoO6-Mo2C-C / C photoelectric catalyst as well as preparation method and application thereof

    CN119144996A